Gut microbiome-derived phenyl sulfate contributes to albuminuria in diabetic kidney disease - Koichi Kikuchi (Nature Portfolio, 2019)
Diabetes is a major cause of kidney disease. Here Kikuchi et al. show that phenol sulfate, a gut microbiota-derived metabolite, is increased in diabetic kidney disease and contributes to the pathology by promoting kidney injury, suggesting phenyl sulfate could be used a marker and therapeutic target for the treatment of diabetic kidney disease.